2008
DOI: 10.2334/josnusd.50.259
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind randomized clinical trial of subgingival minocycline for chronic periodontitis

Abstract: The purpose of this study was to evaluate the presence of A. actinomycetemcomitans, P. gingivalis, P. intermedia, E. corrodens and F. nucleatum in 30 subjects with chronic periodontitis treated by scaling and root planing (SRP) plus minocycline (test group) during 12 months with regular trimester maintenance care. Additionally, we evaluated whether the beneficial effects of the therapy on the microbial flora persisted for 24 months. The test group (n = 15) and the control group [SRP plus placebo (n = 15)] were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Clearly, biofilm is represented by a complex consortium of bacteria, including pathogenic species that can be detected in lower proportions among periodontally healthy individuals. That periodontal pathogens can be found in distinct clinic conditions demonstrates that these bacteria are members of the indigenous microbiota 20,27,28 . However, it should be considered that some species have been associated with the type and severity of periodontitis 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, biofilm is represented by a complex consortium of bacteria, including pathogenic species that can be detected in lower proportions among periodontally healthy individuals. That periodontal pathogens can be found in distinct clinic conditions demonstrates that these bacteria are members of the indigenous microbiota 20,27,28 . However, it should be considered that some species have been associated with the type and severity of periodontitis 7 .…”
Section: Discussionmentioning
confidence: 99%
“…That periodontal pathogens can be found in distinct clinic conditions demonstrates that these bacteria are members of the indigenous microbiota. 20,27,28 However, it should be considered that some species have been associated with the type and severity of periodontitis. 7 Quantitative analyses have helped to better understand the relationship between microbiota and periodontal status and differentiate colonization from infection, in addition to making more clear the influence of demographic and behavioral factors in this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies, only four reported the microbiological outcomes by numeric results on tables. 25,26,27,28 Real-time PCR: Kolbe et al 27 showed a non-significant trend to decrease the quantities (amounts: log 10 ± SEM) of P. gingivalis (1.6 ± 1.4 to 1.0 ± 1.4) and T. forsythia (4.9 ± 3.6 to 4.7 ± 3.8) from PMP baseline to 6 months, respectively, and stability for A. actinomycetemcomitans (2.7 ± 3.1 to 2.7 ± 2.5). There were no differences over time in the percentage of sites harboring T. forsythia and A. actinomycetemcomitans, whereas a significant decrease in the frequency of P. gingivalis was observed.…”
Section: Spg + Sbg Resultsmentioning
confidence: 99%
“…(0.25-8 μg/ml), Pseudomonas aeruginosa (64-128 μg/ml) and Candida genus between (0.25-16 μg/ml) [36]. Clinical trials on subgingival minocycline in chronic periodontitis subjects showed that the scaling followed by subgingival minocycline is effective in reducing periodontal pathogens in chronic periodontitis [37,38]. Also, the effect of minocycline on cell survivals in cell lines showed that cell survivals were not decreased when the cells were treated with minocycline at 10 M and this concentration is greater than the MIC 90 doses of most periodontopathogens [39].…”
Section: Characteristics Of Minocycline Hclmentioning
confidence: 98%